2017
DOI: 10.2337/dc16-0995
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Reducing Driving Mishaps Among Drivers With Type 1 Diabetes

Abstract: OBJECTIVETwo aims of this study were to develop and validate A) a metric to identify drivers with type 1 diabetes at high risk of future driving mishaps and B) an online intervention to reduce mishaps among high-risk drivers.RESEARCH DESIGN AND METHODSTo achieve aim A, in study 1, 371 drivers with type 1 diabetes from three U.S. regions completed a series of established questionnaires about diabetes and driving. They recorded their driving mishaps over the next 12 months. Questionnaire items that uniquely disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Studies have variably shown increased rates of driving accidents in drivers with type 1 diabetes, although this may be due to an overrepresentation of a particular subgroup of drivers with poorer glycemic awareness . Studies have also shown reductions in automobile accidents following specific hypoglycemia awareness training programs …”
Section: Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have variably shown increased rates of driving accidents in drivers with type 1 diabetes, although this may be due to an overrepresentation of a particular subgroup of drivers with poorer glycemic awareness . Studies have also shown reductions in automobile accidents following specific hypoglycemia awareness training programs …”
Section: Drivingmentioning
confidence: 99%
“…120 Studies have also shown reductions in automobile accidents following specific hypoglycemia awareness training programs. 121 The young person who plans to obtain a driving license should be advised on the appropriate regulations and in particular:…”
Section: Drivingmentioning
confidence: 99%
“…The remaining concepts measured are also of great importance in the research and clinical follow-up of patients with diabetes: attitude towards diabetes, emotional distress, hope, perception of disease severity. However, some common barriers faced by patients with diabetes, such as beliefs, relationship with health care professionals, lifestyle changes (50), physical activity (51), and risk of driving (52) have not been evaluated in Brazilian diabetic populations and still require crosscultural adaptation and validation in order to be ready for using.…”
Section: Diabetes-specific Surveys In Brazilmentioning
confidence: 99%
“…To assist this task, Cox and colleagues have developed an 11-item questionnaire to identify high-risk drivers and have shown that an online intervention reduced the incidence of driving mishaps over a 12-month period. 5 How are people with diabetes licensed to drive motor vehicles in different parts of the world?…”
Section: Can We Identify Drivers With Diabetes At Risk Of Road Traffimentioning
confidence: 99%